Insufficient Lycopene Intake Is Associated With High Risk of Prostate Cancer: A Cross-Sectional Study From the National Health and Nutrition Examination Survey (2003–2010) - Lu, You; Edwards, Andrea; Chen, Zhong; Tseng, Tung-Sung; Li, Mirandy; Gonzalez, Gabrielle V.; Zhang, Kun (Frontiers in Public Health, 2021)
Although lycopene intake and risk of prostate cancer have been explored for decades, recent studies show that non-Hispanic Black Prostate Cancer (PCa) patients benefit less than non-Hispanic White patients from a lycopene intake intervention program. This study examined whether a lycopene intake related racial disparity exists in reducing the risk of PCa in healthy adults. Data on healthy, cancer-free non-Hispanic Black (NHB) men (n=159) and non-Hispanic White (NHW) men (n=478) from the 2003–2010 NHANES dataset were analyzed. Total lycopene intake from daily diet, age, living status, race/ethnicity, education level, poverty income ratio, Body Mass Index, and smoking status were studied as independent variables. The combination of total Prostate-Specific Antigen (PSA) level and the ratio of free PSA were set as criteria for evaluating the risk of PCa. Multivariable logistic regression was used in race-stratified analyses to compute odds ratios (OR) and 95% confidence intervals (95% CI) comparing high PCa risk with low PCa risk. We found, in the whole population, race/ethnicity was the only factor that influenced lycopene intake from daily diet. NHB men consumed less lycopene than NHW men (3716 vs 6487 (mcg), p=0.01). Sufficient lycopene intake could reduce the risk of PCa (OR: 0.40, 95% CI: 0.18-0.85, p=0.02). Men aged between 66 to 70 had high PCa risk (OR: 3.32, 95% CI: 1.12-9.85, p=0.03). Obesity served as a protective factor against the high risk of PCa (OR: 0.25, 95% CI: 0.12-0.54, p=0.001). NHW men aged between 66 to 70 had a high risk of PCa (OR: 4.01, 95% CI: 1.02-15.73, p=0.05). Obese NHW men also had lower risk of PCa (OR: 0.18, 95% CI: 0.07-0.47 p=0.001). NHB men had a high risk of PCa compared to NHW men (OR: 2.27, 95% CI: 1.35-3.81 p=0.004). NHB men who were living without partners experienced an even higher risk of PCa (OR: 3.35, 95% CI: 1.01-11.19 p=0.07). Sufficient lycopene intake from daily food could serve as a protector against PCa. Such an association was only observed in NHW men. Further studies are needed to explore the dose-response relationship between lycopene intake and the association of PCa risk in NHB men.